Spatial-temporal characteristics of meteorological drought and its relationship with circulation indices over Songhua River Basin, China - Jiale Xu; Xiumei Li; Jianwen Xue; Xiangzhou Dou; Wenqing Wu; Gaopeng Wu; Qiang Zhao (Journal of Water and Climate Change, 2024)
Global warming has increased the risk of meteorological drought and associated hazards. Based on daily data from 35 meteorological stations in the Songhua River Basin (SRB) collected from 1960 to 2019, this study applied the standardised precipitation evapotranspiration index (SPEI) and used the ensemble empirical mode decomposition (EEMD) method and Pettitt's mutation test to perform a partitioned segmentation analysis of the multi-temporal and spatial variations in the meteorological droughts affecting the basin in terms of frequency and intensity, and discussed the relationship between the atmospheric circulation index and meteorological drought. The results showed that the overall meteorological drought trends shifted from a drought to a humid trend from 1960 to 2019. The drought in the basin had periods of 3, 6.7, 15, and 30 years, with mutation points in 1968, 1980, 1997, and 2012. The drought trend in Regions I and IV of the entire basin was enhanced, while that in Regions II, III, and V was weakened. Drought in the basin was strongly influenced by the Arctic Oscillation (AO) and Southern Oscillation Index (SOI). HIGHLIGHTS The SRB shifted from a drought trend to a wet trend from 1960 to 2019.; High-frequency and high-intensity drought areas are mainly distributed in Regions I and IV.; Drought in the basin is greatly influenced by AO and SOI.;